2022
DOI: 10.3390/ani12192643
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Untargeted Metabolomics Reveal the Potential of Tetradesmus obliquus, Chlorella vulgaris and Nannochloropsis oceanica as Valuable Nutrient Sources for Dogs

Abstract: The growing pet population is questioning the sustainability of the pet food system. Although microalgae may constitute a more sustainable food resource, the assessment of their potential for canine diets is almost non-existent. The present study aimed to evaluate the potential of three microalgae species (Tetradesmus obliquus, Chlorella vulgaris and Nannochloropsis oceanica) grown locally in industrial photobioreactors as alternative food resources for dogs. A detailed characterization of their nutritional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 99 publications
1
17
0
Order By: Relevance
“…However, its protein content is highly dependent on the cultivation conditions and can be as low as 13.6% DM [ 24 ] under nitrogen-limiting conditions [ 25 ]. The protein quality of CV is high, as it contains all essential amino acids, including a significant amount of leucine and lysine (average of 9 to 10% of total amino acids) [ 26 , 27 ]. Lysine, in particular, is a limiting amino acid for poultry and swine, and can be found in C. vulgaris at levels as high as 10.4 to 13.2% [ 26 , 27 ].…”
Section: Nutritional Composition Of Chlorella Vulgarismentioning
confidence: 99%
See 3 more Smart Citations
“…However, its protein content is highly dependent on the cultivation conditions and can be as low as 13.6% DM [ 24 ] under nitrogen-limiting conditions [ 25 ]. The protein quality of CV is high, as it contains all essential amino acids, including a significant amount of leucine and lysine (average of 9 to 10% of total amino acids) [ 26 , 27 ]. Lysine, in particular, is a limiting amino acid for poultry and swine, and can be found in C. vulgaris at levels as high as 10.4 to 13.2% [ 26 , 27 ].…”
Section: Nutritional Composition Of Chlorella Vulgarismentioning
confidence: 99%
“…The dried biomass of CV also contains significant amounts of ash, reaching up to 27.3% [ 28 ]. The ash is rich in essential minerals such as phosphorus, potassium, iron, manganese, and zinc [ 24 , 26 ]. While there may be some concern about heavy metal toxicity in Chlorella spp., studies have shown that such toxic elements, including arsenic, cadmium, and mercury, are present in concentrations as low as 0.59–1.1 mg/kg, 0.01–0.10 mg/kg, and 0.02–0.10 mg/kg, respectively, and no lead was detected [ 25 ].…”
Section: Nutritional Composition Of Chlorella Vulgarismentioning
confidence: 99%
See 2 more Smart Citations
“…Grains are an important carbohydrate source in dog diets, with most extruded pet foods containing 20–50% carbohydrates [ 31 ]. Nutritionally, carbohydrates are not essential nutrients [ 32 ]; yet, when compared to animal protein or fats, carbohydrates are an extremely economical energy source for use in pet foods [ 33 ]. Although grains are a widely used carbohydrate source within the pet food industry, many companion animal owners are concerned about feeding their pets grains, and studies on the safety of carbohydrate sources available in dog foods are limited [ 34 ].…”
Section: Introductionmentioning
confidence: 99%